2005
DOI: 10.1111/j.1365-2230.2005.01768.x
|View full text |Cite
|
Sign up to set email alerts
|

Contact dermatoses in healthcare workers: reduction in type I latex allergy in a UK centre

Abstract: Natural rubber latex (NRL) allergy has been recognized as a public health concern. NRL allergy frequently occurs in healthcare professionals. In this retrospective study we report the changing frequency of Type I NRL allergy amongst healthcare workers suffering from hand dermatitis referred to our department between 1996 and 2003. We identified 224 healthcare workers from the patch test database with a diagnosis of hand dermatitis who had undergone NRL skin prick testing (SPT). We report the SPT results, patch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 19 publications
2
10
1
Order By: Relevance
“…A study in Germany reported a high prevalence of 8% among 226 dental students who had only been exposed to exclusive powder-free latex gloves 30. Similarly in the UK despite a total ban on powdered latex gloves Clayton and Wilkinson31 found a 10% prevalence of latex sensitisation in HCWs. It is also not clear to what extent the aeroallergens released by colleagues using powdered latex gloves influence this finding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study in Germany reported a high prevalence of 8% among 226 dental students who had only been exposed to exclusive powder-free latex gloves 30. Similarly in the UK despite a total ban on powdered latex gloves Clayton and Wilkinson31 found a 10% prevalence of latex sensitisation in HCWs. It is also not clear to what extent the aeroallergens released by colleagues using powdered latex gloves influence this finding.…”
Section: Discussionmentioning
confidence: 99%
“…This has proven to reduce latex-induced clinical outcomes. Even with this intervention, studies in Western countries such as Germany and the UK have shown that the risk of latex sensitisation still exists and more needs to be carried out to protect HCWs 30 31…”
Section: Introductionmentioning
confidence: 99%
“…Type IV reactions are generally considered more common than type I reactions and a high prevalence rate of type IV allergy among healthcare workers has been highlighted in several surveys [3,23,85,86]. Skin patch testing using NRL glove extracts can demonstrate a response to both specific protein allergens and the chemicals present and so will be a combination of both type I and IV reactions.…”
Section: Prevalence Of Type IV Allergymentioning
confidence: 99%
“…In Europe, thiurams in gloves are common allergens with rates of sensitization ranging from 2% to 25% (1–3). Sensitization to these compounds is a common work‐related problem, especially for the recent increase in use of latex gloves in healthcare workers and also in food workers, such as bakers, cooks, and butchers (4, 5). However, rare professional sources of thiuram allergy are reported in workers not wearing gloves: a painter (TEDT‐based bactericide in water‐based paint) (6), a farmer (boots and seed dressings) (7), a golfer (fungicide) (8) and a shepherdess (lambing ring) (9).…”
Section: Discussionmentioning
confidence: 99%